The factors of crime prevention through social development for a higher quality of life / Noor Ashikin Mohamad Bahari, Halmi Zainol and Siti Rasidah Md Sakip - Mohamad Bahari, Noor Ashikin; Zainol, Halmi; Md Sakip, Siti Rasidah (2021)
Crime and crime prevention have recently become crucial issues that are increasingly being debated all across the globe. The occurrence of crime is a constraint towards a higher quality of life because it leads to a feeling of fear. In dealing with the crime issues, the most important thing that needs to be clarified is the root causes of crime incidence to ensure that crime can be understood in a comprehensive manner. The purpose of this paper is to provide an understanding through preliminary research on the key factors that contribute to crime prevention through social development approaches. These cover the kind of factors that can be employed to deter crime for a higher quality of life towards livable communities. A desk study was employed to gather all information needed and to explore the potential of community development strategies that lead to a higher quality of life. In line with the purpose, the objective of this study is to review the related scholarly articles and previous literature in order to identify the key factors that contribute to crime prevention through social development. The study also tries to assess the factors influencing the risks of crime and violence towards a better understanding of the whole context. The ATLAS.ti software was employed to analyze the body of information gathered. To understand the whole context, this paper also outlines the factors that influence the risks of crime and violence. Based on the review, the identified factors of social development crime prevention include preschool program, early school-leaver's program, parenting training, mentoring programs, family and school partnership, anti-bullying initiatives, self-esteem and empowerment, establishment of youth activities, health care assistant, job skills training, drug and alcohol control program and violence reduction campaign. This study is important to nourish the information and knowledge towards crime prevention through community development. At the same time, it will be a source of inspiration and aspiration to all related stakeholders to develop the most effective and comprehensive strategies towards a safer living environment and a higher quality of life based on social development crime prevention approaches.